Perspektif Yuridis Pengaturan Tata Guna Tanah dalam Implementasi Kebijakan Bidang Pertanahan - Iswantoro MH (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2014)
The Land stewardship arrangements in policy implementation refers to theSpatial regulation as the principal rules and adapted to an adjustment program,control, use, and land usage in order to implement spatial planning and governanceareas. Land policy in the land Stewardship is executed with the reference to the UUPAand refers to the Law no. 24 year of 1992 junto. Law no.26 year of 2007 aboutSpatial Planning. The integration of the implementation arrangement and landStewardship is done in coordination of the various institutions that exist in the Regionthat is Bappeda, institutions and the Regional Land Affairs Office. The LandStewardship includes various fields in the setting of the control, use, and utilization ofthe land in the protection region and the cultivated area that is a common reference forLocal Government in taking land policies in their respective regions. This is necessary sothat all the land aspects are able to provide a balance between the carrying capacity ofthe land concerned with economic advances relating to the land use and its exploiting.